HUBUNGAN TINGKAT PENGETAHUAN OSTEOPOROSIS DENGAN PERILAKU PENCEGAHAN OSTEOPOROSIS PADA WANITA PRE MENOPAUSE DI KELURAHAN TIPES SURAKARTA - Ditya Yankusuma Setiani; Rahayu Setyaningsih; Wulan Yuliana Fungky (KOSALA : Jurnal Ilmu Kesehatan, 2015)
The background of this research is Osteoporosis is a disease characterized by reduced bone mass and a change in microarchitecture (the form of micro / subtlest) of bone tissue that result in decreased bone strength and increased bone fragility, leading to brittle bones. From preliminary observations that researchers do in the Village of typhoid in November showed 10 pre-menopausal women who were interviewed 8 of them did not undertake to prevent osteoporosis. Things that cause them not to prevent osteoporosis is ignorance about the dangers of osteoporosis and ignorance about how to prevent. The purpose of the research was to determine Relations Knowledge Level Osteoporosis with Behavioral Prevention of Osteoporosis in Women Pre Menopause in Tipes.The Subject of research were all pre-menopausal women aged 40-50 years with the criteria in the Village Tipes who met the inclusion criteria were already writers set. The sampling technique used is the consecutive sampling technique that is the way the sampling is done by selecting a sample that met the study criteria until a certain time so that the number of samples met. The result of the research are largely pre menopausal women have a high level of knowledge about osteoporosis as many as 32 people (59.3%), the majority of pre menopausal women are 32 women (59.3%) had less active behavior in the prevention of osteoporosis, while women which has the active behavior as much as 22 women (40.7%). From the results of Chi-Square test SPSS version 18.0 with Î± = 5% (0.05), obtained p equal to 0.002 so that the value of p <0.05, which means that Ho is rejected and Ha accepted. Conclusion of the research was the existence of relationship the level of knowledge about osteoporosis with prevention behaviors pre menopausal osteoporosis in women in Tipes Surakarta.Keywords: Knowledge Level of Osteoporosis, Behavioral Prevention